Teacher Educators Experience Adopting Problem-Based Learning in Science Education - Benjamin Aidoo (MDPI AG, 2023)
Higher educational institutions have utilized problem-based learning (PBL) approaches over the last two decades. The approach has been found to enable educators to adopt different teaching and learning strategies. This study examined how teacher educators have adopted technology integrated PBL in teacher education. The study aimed to understand teacher educators perceptions of adopting the approach in their classrooms. Interviews were conducted with three teacher educators in Ghana. A thematic analysis was used to analyse the data from the interviews. The teacher educators believed integrating PBL into the curriculum emphasizes students learning roles to support their independent and self-directed learning. They also perceived that the PBL approach enabled them to create collaborative learning activities to interact and communicate with students, which can lead to conceptual knowledge development. The educators also indicated challenges such as a lack of beliefs and competence, inadequate resources, and limited time allocation for school inquiry-based lessons.